Spin‐Coating: In Situ Studies of Phase Separation and Crystallization Directed by Marangoni Instabilities During Spin‐Coating (Adv. Mater. 48/2013). (December 2013) - Toolan, Daniel T. W.; Pullan, Nikki; Harvey, Michael J.; Topham, Paul D.; Howse, Jonathan R.
<x xml:space="preserve">Abstract</x> A spherulite of PEO is imaged during spin‐coating using a combination of crossed polarizers and white‐light stroboscopic microscopy. The interplay between the phase separation and crystallization in polymer blends during spin‐coating is investigated by J. R. Howse and co‐workers on page 7033, revealing the appearance of Bernard cells during the phase separation process and that, critically in blends of PS:PEO, phase separation occurs first, which is then followed by crystallization. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>